Effects on Performance, Immunological Response and Short-Chain Fatty Acid Profile in Feces of Nursery Piglets Fed with Organic Acids and Yeast Wall - Cassio Antônio Ficagna; Aleksandro Schafer da Silva; Rafael Domingos Rofino; Emerson Zatti; Tatiane Esposito; Ana Carolina H. Xavier; Roger Wagner; Bianca Fagan Bissacotti; Ronaldo Barbieri Seghetto; Eduardo Mioto Ternus; Diovani Paiano (Animals)
The piglet nursery phase is one of the critical moments in production, especially in the first few weeks after weaning. Growth-promoting antibiotics have always been used in this phase, but the world is banning or limiting the use of antibiotics for this purpose, which has led researchers to seek alternatives, with an emphasis on organic and natural ones. As a result, this study aimed to evaluate whether a combination of organic acids and their derivatives (ammonium formate, formic acid, ammonium propionate, and acetic acid) and yeast wall (mannan oligosaccharides and beta-glucans) in piglet feeding during the nursery phase has positive effects on the SCFA profile in feces and animal health reflected in greater weight gain. A 40-day experiment was conducted in a completely randomized design containing three treatments, each with nine replicates and three piglets per replicate: negative control (NC: without additives), and a combination of organic acids and yeast wall at doses of 1 and 2 kg/ton (AO+YW-1 and AO+YW-2, respectively). Animals received four diets: pre-starter 1 (d1–7), pre-starter 2 (d8–14), starter 1 (d15–25), and starter 2 (d26–40). The animals were weighed on the day of the diet change. Blood and feces were collected on days 14 and 40 of the experiment. Piglets from the AO+YW-1 group showed more significant weight gain than NC. Feed intake was higher in piglets from the AO+YW-1 group considering the first 25 days of the experiment compared to NC; there was no treatment effect on feed conversion. Piglets from NC had higher levels of C-reactive protein and ferritin, while AO+YW-2 had higher levels of interleukin 10 and lower levels of TNF-α. A greater quantity of SCFA was observed in the feces of piglets on d40, related to the changes in propionic, butyric, isovaleric, and valeric acids. Therefore, the combination of organic acids and yeast wall used at a dose of 1 kg/ton proved to be an additive option for the diet of piglets in the nursery phase to enhance weight gain and reduce the number of doses of injectable antibiotics.